Patron-Client in Changing Livelihood from Rubber Plant to Palm - Yuda, Garuda Parampara (Indonesian Journal of Multidisciplinary Science, 2023)
Rubber gardening for people in several regions of West Kalimantan is the main livelihood. One of them is in Sei Kembayau Village. For generations, rubber gardening has been the livelihood of the villagers. Rubber plants have actually been passed down from generation to generation. The patron-client concept that currently exists is the basic foundation in survival and has been attached to rubber plantations in the community. This paper aims to see the patron-client pattern from the change in livelihood of rubber plants to oil palm plants. This study used ethnographic research methods. Take a holistic approach and describe it in depth or detail to obtain a genuine person's point of view. Tauke patron-clients and subordinates are still well established as an economic concept of the Sei Kembayau Village community, even though there is already a KUD present in the community as support for the palm oil economy. So that subordinates will still get social security from every Tauke as their patron.